Application of Test Instrument Designs for Momentum and Impuls In Achieving The Conceptual and Procedural Knowledge of High School Students - Maharani, Nur; Manik, Imaniyah (Journal of Learning and Technology in Physics, 2020)
This study aims to develop momentum and impulse material test instruments on the achievement of high school students' conceptual and procedural knowledge learning outcomes. The research method used in the design of test instruments is to determine the purpose of the test, compile the grid, choose the form of the test instrument, determine the length of the test instrument, validate the test and test the test to find out the test results. The test instrument was used to assess students' conceptual and procedural knowledge abilities on the material of momentum and impulses. The subject of the study was the test instrument. This research successfully developed a test instrument for momentum and impulse material on the achievement of learning outcomes of high school students' conceptual and procedural knowledge.